Electricity self-sufficiency of single-family houses in Germany and the Czech Republic. (15th October 2018) - Ramirez Camargo, Luis; Nitsch, Felix; Gruber, Katharina; Dorner, Wolfgang
Highlights: PV and battery system sizes for electricity self-sufficient SFHs are estimated. The study relies on high resolution regional reanalysis data for two decades. Results cover low populated areas of Germany and the Czech Republic in 1 km 2 resolution. Battery sizes range between 8 and 11.5 kWh in a cost optimal scenario. PV modules of up to 30 kWp are necessary in a cost optimal scenario. Abstract: Motivated by a research project that studies the future of the energy system in rural areas at the border between Germany and the Czech Republic, and by the publication of the COSMO-REA high-resolution regional reanalysis data sets for Europe in 2017, this study presents a methodology for generating maps indicating minimum battery and photovoltaics sizes for self-sufficient single-family houses. The methodology consists of three subsequent parts: First, spatiotemporal data sets of electricity demand for single-family houses in rural and low-density urban areas are generated. Second, spatiotemporal data sets of photovoltaics potential are computed based on (a) a technical photovoltaics model, (b) two decades of hourly solar irradiance and temperature data, and (c) snow cover data from the Land Surface Analysis Satellite Applications Facility. Third, a linear optimization model serves to define photovoltaics and battery systems sizes and to generate the corresponding maps. The resulting maps cover Germany and the Czech Republic and are generated for 18 technical and weather-dependent scenarios. The results show how challenging it could be to achieve complete independence from the grid in certain locations. Especially relevant for the sizing of the systems are long periods (several days in a row) of low photovoltaic energy generation due to overcast sky conditions or snow cover of the panels. Furthermore, the results offer a scientifically based source of information for sizing photovoltaics and battery systems in the two countries.